STAGES OF TECHNICAL REVOLUTION AND ITS SOCIO-PHILOSOPHICAL IMPORTANCE - Abdullaevich, Kushakov Fayzulla (PT. Antis International Publisher, 2024)
This article examines the transformative discoveries in production, industry, and technology from the 17th to the 20th centuries, highlighting their profound impact on human life. General Background: The period marked a pivotal shift in economic and political relations, often referred to as the